PERAN DAN GUGATAN MASYARAKAT MENURUT UNDANG-UNDANG NO. 23 TAHUN 1997 TENTANG PENGELOLAAN LINGKUNGAN HIDUP - Eka Yuliastuti (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2019)
The purpose of this study is to find out how the role of the community and community lawsuits according to Law No. 23 of 1997 concerning Environmental Management. The research method used in this study is a qualitative method. While the approach uses the normative juridical approach. The type of data used is primary data and secondary data. Data collection methods by interview and documentation. The process of community participation must be open to the public, community participation will affect the credibility and accountability of the relevant institutions. By documenting the actions of this State decision, it is expected to be able to provide satisfactory means if the public and the court will examine the considerations that have been taken when making the decision. The right of community claim can be filed through NGOs if there are similarities in facts or events and the legal basis and types of claims between group representatives and group members. As for environmental organizations, they can file a lawsuit if they meet the requirements, among others in the form of legal entities, confirm in their articles of association that the organization was established for the purpose of preservation of environmental functions, and have carried out concrete activities with a statute of at least 2 years